Optimization of torrefaction on Torrefied Biochar from Oil Palm Empty Fruit Bunches (OPEFB) for potential biomass energy - Rose Nadiah Abu Hasan (2020)
The worldwide demand for energy and energy use is increasing rapidly. The biomass resource was chosen as a renewable energy sources based on the abundance of oil palm waste generated monthly. The aim of this study is to find an optimal value of torrefection process on the torrefied biochar from the oil palm empty fruit bunches (OPEFB) in order to produce biomass energy source by using the Box-Behnken design of Response Surface Methodology (RSM). In this study, OPEFB were torrefied based on the three dependent variables which are particle size of 250-750 µm, holding temperature of 200-300°C and residence time of 30-90 minutes. Torrefied biochar were being optimized in regards of six independent variables which were mass yield, calorific value, fixed carbon, moisture content, volatile matter and ash content. The optimization process from the RSM showed that the most optimal value for torrefied OPEFB biochar were at 750 µm, 274°C and 90 minutes of torrefaction in order to produce a high energy content of biomass.